PORE SPACE CHARACTERIZATION USING MICRO CT SCAN METHOD IN IGNEOUS ROCKS FROM TENGGER VOLCANIC COMPLEX - NIM: 12312020, WIDYA
Study on volcanic rocks generally observed at its fraction which consists of rock structure, texture, mineralogy, and other characterization through thin incisions. Meanwhile, pore space is ignored because itÃ‚Â’s too small. Pore space studied by using thin incision will be difficult because it has to make thin incisions many times. Thin incisions method is less practical, high costs, and longtime process. This study is discussed about pore and its characterization by using Micro CT Scan Method. Micro CT Scan method is conducted by scanning object without damaging the sample. This method is also cheaper, practicable, and short time process. Sample used in this study is taken from lava stream on Sapikerep, Tengger Volcanic Complex. Pore space characterization which discussed in this study is open pore space and closed pore space. Pore space is observed by using 2-dimensional and 3-dimensional images. 2-dimensional image observes vertical area of the sample meanwhile 3-dimensional image observes the volume of open pore space and closed pore space as additional information. Both area and volume is using percentage scale. Orientation and shape of the pore are also observed. Pore orientation observed by using 2-dimensional and 3-dimensional data and images. Meanwhile, the pore shape observed by using only 3-dimensional images, whether the tendency is spherical or ellipsoid. From this study, pore space characterization is related to rock deformation process based on computational data from Micro CT Scan Method, scanned images, and literature studies. It is concluded that pore studies are important to know rock cycle and rock physical properties especially volcanic or igneous rocks.